Formulation, characterization, optimization, and in-vivo performance of febuxostat self-nano-emulsifying system loaded sublingual films - Basant A. Habib; Amina S. Abd El-Samiae; Boushra M. El-Houssieny; Randa Tag (Taylor & Francis Group, 2021)
Febuxostat (FXS) is a potent antigout drug with poor water solubility and relative high first-pass effect leading to moderate oral bioavailability (<49%). This study aimed to increase FXS solubility and bioavailability by optimizing sublingual fast-dissolving films (SFs) containing a selected FXS self-nano-emulsifying system (s-SNES) previously prepared by our team. The s-SNES was loaded into SFs by solvent casting technique. A full factorial design (32) was applied to study the effects of polymer and plasticizer types on mechanical characteristics and the dissolution profile of FXS from the SFs. Numerical optimization was performed to select the SF having highest desirability according to predetermined characteristics. The optimized SF (O-SF) contained 1 g of s-SNES, polyvinylpyrrolidone K30 (6%w/v), polyethylene glycol 300 (20%w/w of polymer wt.), and Avicel PH101 (0.5%w/v). O-SF showed good permeation of FXS through sheep sublingual tissue. Storage of O-SF for three months showed no significant change in the FXS dissolution profile. In-vivo performance of O-SF in rabbits was compared to that of oral marketed tablets (Staturic® 80 mg). A cross-over design was applied and pharmacokinetic parameters were calculated after ensuring absence of sequence effect. Statistical analysis revealed better performance for O-SF with significantly higher Cmax, AUC0-24, AUC0-∞, apparent t1/2 together with lower tmax, and apparent kel than marketed tablets. Relative bioavailability of O-SF compared to the marketed tablet was found to be 240.6%. This confirms the achievement of the study aims of improving dissolution rate and bioavailability of FXS using a patient-wise convenient formula.